2007
DOI: 10.1016/j.appdev.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Contextual risk and parenting as predictors of effortful control and social competence in preschool children

Abstract: Using a short-term longitudinal design (6 months), this study examined cumulative contextual risk as a predictor of effortful control (EC) and social competence in a community sample of children (N = 80, ages 33-40 months at time 1). Maternal parenting was examined as a mediator of contextual risk. EC was assessed using laboratory tasks, and parenting was assessed using observational ratings. Time 1 contextual risk was negatively related to time 2 EC after controlling for time 1 EC. Mothers' limit setting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
327
2
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(380 citation statements)
references
References 64 publications
30
327
2
11
Order By: Relevance
“…Multiple family and social risk factors, including low income, low maternal education and low occupational skills, have been shown to adversely predict children's achievement (Ackerman, Brown, & Izard, 2004;Burchinal, Roberts, Zeisel, Hennon, & Hooper, 2006;Lipina, Martelli, Vuelta, & Colombo, 2005;McLoyd, 1998). Although less extensively examined, a number of studies also suggest the adverse effects of socioeconomic disadvantage on children's behavioral regulation skills (Evans & Rosenbaum, 2008;Lengua, Honorado, & Bush, 2007;Mezzacappa, 2004;Noble, Norman, & Farah, 2005;Wanless, McClelland, Tominey, & Acock, 2011). In one study examining the effects of socioeconomic status (using a composite of income, occupational and educational status), results suggested that socially disadvantaged children performed less proficiently in behavioral regulation than their more advantaged peers (Mezzacappa, 2004).…”
Section: Socioeconomic Risk Academic Achievement and Behavioral Regumentioning
confidence: 99%
“…Multiple family and social risk factors, including low income, low maternal education and low occupational skills, have been shown to adversely predict children's achievement (Ackerman, Brown, & Izard, 2004;Burchinal, Roberts, Zeisel, Hennon, & Hooper, 2006;Lipina, Martelli, Vuelta, & Colombo, 2005;McLoyd, 1998). Although less extensively examined, a number of studies also suggest the adverse effects of socioeconomic disadvantage on children's behavioral regulation skills (Evans & Rosenbaum, 2008;Lengua, Honorado, & Bush, 2007;Mezzacappa, 2004;Noble, Norman, & Farah, 2005;Wanless, McClelland, Tominey, & Acock, 2011). In one study examining the effects of socioeconomic status (using a composite of income, occupational and educational status), results suggested that socially disadvantaged children performed less proficiently in behavioral regulation than their more advantaged peers (Mezzacappa, 2004).…”
Section: Socioeconomic Risk Academic Achievement and Behavioral Regumentioning
confidence: 99%
“…Similarly, developmental researchers have hypothesized that the delays in EF development associated with growing up in poverty may have their roots in early socialemotional experiences, specifically in low rates of sensitive-responsive caregiving that reduce the child's exposure to opportunities for sustained joint attention, language input, and effective scaffolding of early emotion regulation (Goldsmith & Rogoff, 1997;Lengua et al, 2007). Adult responses to child emotional arousal may be particularly important, as supportive adult responses may promote emotional understanding and provide the child with external regulation that can be imitated and internalized (Havighurst, Harley, & Prior, 2004;Kochanska et al, 2000).…”
Section: Intervention Designs To Promote Efs and Self-regulationmentioning
confidence: 99%
“…In addition, EF development depends, in part, upon sensitive-responsive caregiving and opportunities for guided exploration of the social and physical environment, fostering sustained joint attention, emotional understanding, planning, and problem-solving skills (Goldsmith & Rogoff, 1997;Lengua, Honorado, & Bush, 2007;Kochanska et al, 2000). When children experience the factors associated with family poverty, including maternal depression, low levels of social support, stressful life events, and exposure to violence, they are more likely to display delays in the development of EF (Goldsmith & Rogoff, 1997;Lengua et al, 2007;Li-Grining, 2007). For these reasons, school readiness interventions designed to reduce the delays associated with socioeconomic disadvantage may need to attend more carefully to EF development to better understand and maximize intervention impact.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…선행연구에 따르면 유 아의 성 (Lee, 2004;Yang, 2007), 연령 (Yang, 2007), 기 질 (Bae & Lim, 2013;Yang, 2007)과 같은 개인적 특성과 가정환경, 어머니의 양육행동, 어머니-유아의 관계의 질과 같은 양육 관련 변인 (Lee, 2004;Lee & Seo, 2006;Moon, 2007;Song, 2004;Yang, 2007), 유아교육기관의 질적 측면 (Ahn, 2002;Lee, 2001 (Bornstein & Lamb, 2008), 이때 신뢰와 애정 및 관심과 기쁨이 상호 균형을 이룰 때 유아의 발달 에 긍정적인 도움이 된다 (Emde, 1980). 어머니와 유아 간 정서적인 교류는 정서의 표현과 의사소통에 있어서의 어 머니와 유아 간 상호성의 양식을 의미하는데 (Bornstein & Lamb, 2008), Biringen et al (1998)은 민감성 (Ainsworth et al, 1978)과 유아의 자율성을 촉진시키는 어머니의 정 서적 가용성 (Emde, 1980;Mahler et al, 1975) (Denham, et al, 1991;Dumas & Lafreniere, 1993;Kwon, 2002) (Dennis, 2006;Kochanska et al, 2000;Kochanska et al, 2008;Lengua, et al, 2007;Little & Carter, 2005;Rakes et al, 2007;Volling et al, 2002). (Caspi et al, 1995;Hill, 2003;Lengua et al, 2007;Raver et al, 1999), 교사의 지시를 잘 따르며, 정 해진 시간에 과제를 잘 마무리하며, 집단에서 자신감을 잘 보이고 적절하게 대응하며 교사와의 갈등 상황에서 감 정을 잘 조절하며 (Moon, 2010), 학교생활을 좋아하는 것 으로 나타났다 (Valente, et al, 2007).…”
Section: 유아가 교육기관에 적응하는 데는 많은 요인들이 영향unclassified